2015
DOI: 10.1016/j.schres.2015.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for decreased synaptic efficacy in the postmortem olfactory bulb of individuals with schizophrenia

Abstract: Multiple lines of evidence suggest altered synaptic plasticity/connectivity as a pathophysiologic mechanism for various symptom domains of schizophrenia. Olfactory dysfunction, an endophenotype of schizophrenia, reflects altered activity of the olfactory circuitry, which conveys signals from olfactory receptor neurons to the olfactory cortex via synaptic connections in the glomeruli of the olfactory bulb. The olfactory system begins with intranasal olfactory receptor neuron axons synapsing with mitral and tuft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 79 publications
(102 reference statements)
1
6
0
Order By: Relevance
“…Similar significant reductions in SNAP25 expression in schizophrenia measured with quantitative IHC have also been reported in other brain regions including ventromedial caudate (VMC) and Nucleus accumbens (NAc), [53] and glomeruli of olfactory bulb [37••]. However one study looking at the hippocampus using Western blotting found no significant changes in SNAP-25 between schizophrenia and controls.…”
Section: Introduction/backgroundsupporting
confidence: 55%
See 2 more Smart Citations
“…Similar significant reductions in SNAP25 expression in schizophrenia measured with quantitative IHC have also been reported in other brain regions including ventromedial caudate (VMC) and Nucleus accumbens (NAc), [53] and glomeruli of olfactory bulb [37••]. However one study looking at the hippocampus using Western blotting found no significant changes in SNAP-25 between schizophrenia and controls.…”
Section: Introduction/backgroundsupporting
confidence: 55%
“…Reductions in synaptophysin expression in schizophrenia have also been reported in different brain regions by various groups including, in the left thalamus using radioimmunoassay by [34] and in the medial temporal lobe using immunoradiography [35]. Furthermore synaptophysin immunoreactivity was significantly reduced in both the inner and outer molecular layers of the dentate gyrus [36] and also in the glomeruli of the olfactory bulb [37••]…”
Section: Introduction/backgroundmentioning
confidence: 84%
See 1 more Smart Citation
“…Olfactory bulb volume has been found to be smaller in schizophrenia ( Turetsky et al, 2003 ). A postmortem study showed decreased synaptic efficacy in the olfactory bulb of schizophrenia patients ( Egbujo et al, 2015 ). Smaller olfactory bulb volume has also been seen in first-degree relatives of schizophrenic patients ( Kamath et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, an increasing body of evidence is locating PSD alterations in specific brain sites. In post-mortem brain samples from schizophrenia patients, significant changes in key PSD molecules (i.e., PSD-95, Homer 1a, Homer 1b, Preso) have been demonstrated in multiple brain regions, including the hippocampal CA1 region, the prefrontal cortex, and the olfactory bulb [ 96 ]. Exact delivery of PSD-targeting therapeutic agents in brain subdivisions or cell types implicated in disease pathophysiology may be crucial to maximize pharmacological efficacy and/or minimize untoward effects.…”
Section: Novel Putative Therapeutic Strategies Based On Psd Molecumentioning
confidence: 99%